Association of dry eye tests with extra-ocular signs among 3,514 participants in the Sjögren’s Syndrome International Registry - Bunya, Vatinee Y. (Am J Ophthalmol, 2016)
PURPOSE: To identify a screening strategy for dry eye patients with a high likelihood of having Sjogren's syndrome (SS) through the evaluation of the association of ocular surface tests with the extraocular signs used for the diagnosis of SS. DESIGN: Multi-center cross-sectional study. METHODS: The Sjogren's International Clinical Collaborative Alliance (SICCA) registry enrolled 3,514 participants with SS or possible SS from 9 international academic sites. Ocular surface evaluation included Schirmer I testing, tear break-up time (TBUT), and staining of the cornea (0 to 6 points) and conjunctiva (0 to 6 points). Multivariate logistic regression analysis was performed to identify predictive factors for: 1) histopathologic changes on labial salivary gland (LSG) biopsies (positive = focus score of ≥1 focus/4mm(2)) and 2) positive anti-SSA/B serology. RESULTS: The adjusted odds of having a positive LSG biopsy was significantly higher among those with an abnormal Schirmer I test (adjusted OR = 1.26, 95% CI 1.05 to 1.51, P=0.014), positive conjunctival staining (for each additional unit of staining 1.46; 95% CI 1.39 to 1.53, P < 0.001) or corneal staining (for each additional unit of staining 1.14; 95% CI 1.08 to 1.21, P < 0.001). The odds of having a positive serology was significantly higher among those with an abnormal Schirmer I test (adjusted OR=1.3; 95% CI 1.09 to 1.54 P=0.004), and conjunctival staining (adjusted OR=1.51; 95% CI 1.43 to 1.58, P < 0.001). CONCLUSIONS: In addition to corneal staining which was associated with a higher likelihood of having a positive LSG biopsy, conjunctival staining and abnormal Schirmer I testing are of critical importance to include when screening dry eye patients for possible SS as they were associated with a higher likelihood of having a positive LSG biopsy and serology.